Well‐differentiated bronchial neuroendocrine tumors: Clinical management and outcomes in 105 patients. (17th January 2017) - Pericleous, Marinos; Karpathakis, Anna; Toumpanakis, Christos; Lumgair, Heather; Reiner, Jonathan; Marelli, Laura; Thirlwell, Christina; Caplin, Martyn E.
Abstract: Introduction: Bronchial neuroendocrine tumors (NETs) are rare tumors representing approximately 20%‐30% of all neuroendocrine tumors and 2%‐3% of all adult lung cancers. Here, they present a large case series of well‐differentiated bronchial NETs with the aim of investigating the behavior of these tumors and long‐term outcomes. Methods: A retrospective review was performed of 105 patients with bronchial NETs managed in a tertiary referral center in the period between January 1998 and January 2012. Results: Bronchial NETs are commoner in females and the commonest presenting symptoms were cough (13.9%) and dyspnoea (11.6%). Octreoscan TM and Gallium‐68 DOTATATE PET were found to have similar diagnostic sensitivity and FDG PET was more sensitive for higher‐grade tumors. Over a median follow‐up period of 35.5 months mortality rate was 5.7%. The 5‐year survival was 76% and the 10‐year survival was 62%. Female patients survived longer but this difference was not statistically significant ( P = .59). Older age greater than 50 years ( P  = .027), higher levels of Chromogranin A (CgA) ( P  = .034), first‐line treatment with surgery ( P  = .005), ki67 over 10% ( P  = .037), and tumor stage ( P = .036) but not tumor grade ( P = .22), were significantly associated with survival. Discussion: Several factors have been identified which are independently associated with survival including CgA levels greater than 100 pmol/L, tumor stage, age greater than 50, ki67 over 10% and having surgery as first‐line treatment. There was no difference in survival between typical and atypical carcinoids.